The comparative analysis of unscented and extended Kalman filterS for global positioning systems receiver data processing - A. N. Moroz; P. A. Khmarski; S. A. Shaban; O. V. Sidorovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The features of extended and unscented Kalman filters for global positioning systems receiver data processing are considered. The estimation performance of extended and unscented Kalman filters is compared.